The Legal Nature of Remuneration for Periods of Release From the Obligation to Perform Work for Trade Union Activists - Mędrala, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
In this article the Author analizes the issue of legal character of trade union activists released from work, covered by employers. The Author underlines the latest extension of subjective rights in this matter by Polish legislator to other than an employee persons who perform gainful work. In her opinion the remuneration for work, paid by employers at abovementioned basis may be qualified as work-related benefits of a social (even public) nature. In her opinion the current regulations in this matter are questionable in the light of the principle of the independence of trade unions and the principle of proportionality.